Training on Making Biocides Made from Tobacco Leaves in The Dasawisma Group, Mulyorejo Village, Malang City - Mikael Adri Budi Sulistyo; Yekti Sri Rahayu; Erna Atiwi Jaya Esti; Umi Afdah (LPPM Universitas Yudharta Pasuruan, 2022)
This community service activity is carried out to help women in the Dasawisma group RT 03 RW 06 Mulyorejo Village Malang City who have difficulty controlling pests during the practice of cultivating vegetables in their home gardens and vacant lands in their neighborhood. This community service program aims to provide skills to the women of the Dasawisma group in making natural pesticides or biocides to control pests that often attack vegetable crops. The approach method used is training in making tobacco-based biocides and mentoring the application of biocides on some cultivated vegetable crops. The stages of implementing the activities include (1) preparation of tools and materials; (2) Training on making biocides; (3) Assistance in the biocide fermentation process; 4) assistance in the application of biocides to vegetable crops. The results of the community service implementation showed that the women in the Dasawisma group were able to make tobacco-based biocides from fermented products. Application technique by spraying all parts of the plant organs with intervals of spraying biocides three times a week, effective in protecting vegetables during the plant maintenance period. This can be seen from the yield of about 80% of the harvested vegetables that are protected from damage due to pest attacks.